Why size matters: altering cell size. - Saucedo, L.J.; Edgar, B.A. (Current Opinion in Genetics and Development, 2002)
Several genes involved in growth control have lately been demonstrated to exhibit more potent effects on cell size than on cell proliferation. Many of these genes direct protein and ribosomal synthesis, highlighting the interdependence between cell size and macromolecular content. The failure to maintain normal cell size when these genes are deregulated suggests that, in certain contexts, cell growth and division are not coupled or coordinated. Several physiological repercussions of altering cell size have been identified.